Amebic Liver Abscess Diagnosed by Polymerase Chain Reaction in 14 Returning Travelers - Vallois, Dorothée (The American Society of Tropical Medicine and Hygiene, 2012)
Amebic liver abscesses (ALA) are not commonly described in travelers. The ALA diagnosis is usually based on serology and Entamoeba histolytica polymerase chain reaction (PCR) is a new tool. We retrospectively reviewed all ALA cases diagnosed by PCR on the liver abscess pus aspirate of patients admitted in French hospitals between 2007 and 2011. Fourteen cases (10 male, median age 48 years) were included. The median lag time between return and onset of symptoms was 23 days (interquartile range [IQ] 18–24). All patients had an elevated cardiopulmonary resuscitation level, and 11 had leukocytosis. The ALA was multiple in five patients, localized in the right lobe in 12, and higher than 5 cm in 11. Serology was initially negative in one patient, whereas PCR was positive. There was bacterial co-infection in one patient. The outcome was good. Liver puncture allows a rapid diagnosis of ALA with PCR and helps identify the association with a bacterial dual infection.